Perancangan dan Implementasi Pelayanan Puskesmas Pembantu (Pustu) di Desa Kali Cinta Berbasis web - Takeru Kakizaki; Yulina Yulina (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Improving the quality of basic health services is a priority, driving innovation at the Kali Cinta Village Community Health Center (Pustu). This Pustu still faces significant operational challenges, including long queues, inaccessible service information, and manual registration and medical record processes. These conditions result in suboptimal patient data management, frequent data duplication, and slow service delivery, ultimately reducing the efficiency and quality of Pustu services. This study aims to design and implement a computerized web-based Pustu service system. Data collection was conducted through direct observation of service flows, interviews with Pustu staff and the community to understand needs, and a literature review as a theoretical basis. Software development was conducted systematically using the Waterfall method. The expected findings from the implementation of this system are better access to information, accelerated registration processes, and efficient patient data management. The implications of this system are a significant improvement in the quality of health services and community satisfaction in Kali Cinta Village.